Dominant monoallelic variant in the PAK2 gene causes Knobloch syndrome type 2 - Antonarakis, Stylianos E; Holoubek, Aleš; Rapti, Melivoia; Rademaker, Jesse; Meylan, Jenny; Iwaszkiewicz, Justyna; Zoete, Vincent; Wilson, Callum; Taylor, Juliet; Ansar, Muhammad; Borel, Christelle; Menzel, Olivier; et al. (Human molecular genetics, 2021)
Knobloch syndrome is an autosomal recessive phenotype mainly characterized by retinal detachment and encephalocele caused by biallelic pathogenic variants in the COL18A1 gene. However, there are patients clinically diagnosed as Knobloch syndrome with unknown molecular etiology not linked to COL18A1. We studied an historical pedigree (published in 1998) designated as KNO2 (Knobloch type 2 syndrome with intellectual disability, autistic behavior, retinal degeneration, encephalocele). Whole exome sequencing of the two affected siblings and the normal parents resulted in the identification of a PAK2 non-synonymous substitution p.(Glu435Lys) as a causative variant. The variant was monoallelic and apparently de novo in both siblings indicating a likely germ-line mosaicism in one of the parents; the mosaicism, however, could not be observed after deep sequencing of blood parental DNA. PAK2 encodes a member of a small group of serine/threonine kinases; these P21-activating kinases (PAKs) are essential in signal transduction and cellular regulation (cytoskeletal dynamics, cell motility, death and survival signaling and cell cycle progression). Structural analysis of the PAK2 p.(Glu435Lys) variant that is located in the kinase domain of the protein predicts a possible compromise in the kinase activity. Functional analysis of the p.(Glu435Lys) PAK2 variant in transfected HEK293T cells results in a partial loss of the kinase activity. PAK2 has been previously suggested as an autism-related gene. Our results show that PAK2-induced phenotypic spectrum is broad and not fully understood. We conclude that the KNO2 syndrome in the studied family is dominant and caused by a deleterious variant in the PAK2 gene.
Keywords: degenerace retiny; encefalokéla; Retinal Detachment; mutace; odchlípení sítnice; Humans; Mutation; p21-Activated Kinases; Retinal Degeneration; lidé; HEK293 Cells; HEK293 buňky; Encephalocele; p21 aktivované kinasy